Role of Ayurvedic Treatment in Minimizing Gastric Cancer Related Complication: A Case Study - Bhatta, Pramod; Shrestha, Bhakta Man (Journal of Advanced Academic Research, 2017)
The patients usually have the trend to come to the Ayurvedic clinic at the final stage when there is no hope of promising treatment from other conventional system of medicine. One of the major causes of reaching to health facility in the final stage might be the geographical difficulty of Nepal. The patients usually come with the hope of getting support for prolonging life with less pain and misery. In this article role of Ayurvedic treatment in gastric cancer cases are presented analytically. The Purpose of this article is to present the cases that are treated in Private Ayrvedic Clinic, and benefitted in cancer related pain, difficulty and complications with Ayurvedic treatment. The method applied in this study was qualitative longitudinal observation, interview based on the initial and final benefit outcome of the treatment from the Ayurvedic clinic. The findings of treatment are found very encouraging in terms of the signs and symptoms and quality of life they were spending. Patients’ initial problems found to be reduced by the end of observation and interview. It was found that patients were consistently in contact of doctor for the regular treatment. Patients shared that the treatment was less costly compared to its outcome. It seemed that integration of treatment with conventional treatment method might be quite meaningful to reduce gastric cancer related complications and provide better life to the patients. Extensive research on Ayurvedic treatment is necessary to expand the better services to support patients in meaningful way.